Tumour cell survival mechanisms in lethal metastatic prostate cancer differ between bone and soft tissue metastases. Issue 3 (7th June 2013) - Akfirat, Canan; Zhang, Xiaotun; Ventura, Aviva; Berel, Dror; Colangelo, Mary E; Miranti, Cindy K; Krajewska, Maryla; Reed, John C; Higano, Celestia S; True, Lawrence D; Vessella, Robert L; Morrissey, Colm; et al.
Abstract The complexity of survival mechanisms in cancer cells from patients remains poorly understood. To obtain a comprehensive picture of tumour cell survival in lethal prostate cancer metastases, we examined five survival proteins that operate within three survival pathways in a cohort of 185 lethal metastatic prostate metastases obtained from 44 patients. The expression levels of BCL‐2, BCL‐XL, MCL‐1, cytoplasmic survivin, nuclear survivin, and stathmin were measured by immunohistochemistry in a tissue microarray. Simultaneous expression of three or more proteins occurred in 81% of lethal prostate cancer metastases and BCL‐2, cytoplasmic survivin and MCL‐1 were co‐expressed in 71% of metastatic sites. An unsupervised cluster analysis separated bone and soft tissue metastases according to patterns of survival protein expression. BCL‐2, cytoplasmic survivin and MCL‐1 had significantly higher expression in bone metastases (p < 10−5), while nuclear survivin was significantly higher in soft tissue metastases (p = 3 × 10−14). BCL‐XL overexpression in soft tissue metastases almost reached significance (p = 0.09), while stathmin expression did not (p = 0.28). In addition, the expression of MCL‐1 was significantly higher in AR‐positive tumours. Neuroendocrine differentiation was not associated with specific survival pathways. These studies show that bone and soft tissue metastases from the same patient differ significantly in expression of a panel of survival proteins and that with regard to survival protein expression, expression is associated with the metastatic site and not the patient. Altogether, this suggests that optimal therapeutic inhibition may require combinations of drugs that target both bone and soft tissue‐specific survival pathways. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.